Blockchain-based Market Transaction and Islamic Economics: A Bibliometric Analysis - Sandiko Anggoro; Khoirul Umam; Subhan Mawardi (Universitas Muhammadiyah Malang, 2023)
The advent of blockchain technology has led to an exponential growth in the digital world. This study intends to categorize dominant topics related to find out what concepts and dominant themes are massively discussed in studies related to blockchain-based market transaction and Islamic economics. This study was a systematic literature review using the Scopus database from year 2020 to 2023, as the main reference source to consider that this database have a high reputation in the international scientific field. The steps of study was carried out by summarizing various previous studies related to blockchain-based market transaction and Islamic economics in order to find strategies and various in the massive discourse around financial technology. The study found that there were four dominant topics related to this research were: cryptocurrency; market; barrier; and network. This study will contribute to enrich the concepts and dominant themes were massively discussed in studies related to blockchain-based market transaction and Islamic economics.